Capabilities of micro-Raman spectrometry for the identification of uranium ore concentrates from analysis of single particles - Pointurier, Fabien; Fanghänel, Thomas (Vibrational spectroscopy, 2019)
It has been proven, by the analysis of macroscopic amount of materiel pressed into pellets, that Raman spectrometry is a well suited technique to determine precisely the chemical compositions of uranium ore concentrates (UOCs), which is useful information for nuclear forensics and safeguards. However, as in some cases, only low amounts of UOC are available or the sample is a mixture of different UOCs, there is a need to carry out the identification at the individual grain or particle’s level. To evaluate the capability of micro-Raman spectrometry (MRS) for this purpose, 15-30 particles with typical sizes of a few micrometers from five UOCs of known bulk chemical compositions (uranyl peroxide - UP, sodium di-uranate - SDU, ammonium di-uranate - ADU, tri-uranium octo-oxide - TUO, and uranyl hydroxide - UH), production process and origins, were analyzed. Spectra were also compared with the ones obtained with macroscopic amounts of material pressed into pellets. Results show that for some UOCs (SDU, ADU, UH), micro-Raman spectra are reproducible from one particle to another and in good agreement on one side with available bibliographic data and on the other side with Raman spectra performed on macroscopic amounts of UOC. However, spectra of particles from the UP and TUO UOCs show that these compounds are mixtures of three species which were identified. In these cases, an acceptable agreement is obtained between the average Raman spectrum on compressed pellets and the one of most abundant species in analyzed particles. Consequently, an UOC compound or components of a mixture of UOCs can be reliably identified by the analyses of a limited number of isolated particles of a few μm in size by means of MRS.